If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + -44 = -13 Reorder the terms: -44 + s = -13 Solving -44 + s = -13 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + s = -13 + 44 Combine like terms: -44 + 44 = 0 0 + s = -13 + 44 s = -13 + 44 Combine like terms: -13 + 44 = 31 s = 31 Simplifying s = 31
| -4(x+5)+3=6(x+4)+1 | | f/2-19=-17 | | 8x-12=68 | | 6q=-6+7q | | 8x=6x+14 | | 5.85=0.65x | | -8=-(v+4) | | -7+6r=6r+3+r | | 8x-(x+3)(4x-5)=(5+2x)(4-x)-3(x+4) | | 6(8+3x)=174 | | 6y-25=4y+2 | | 17-9x=11+7x | | 69-7x=2x+23 | | h(t)=-16x^2+14 | | -160=8(4m-4) | | 9-7x=113-35x | | -5+5f=-5+8f | | 13x+9=15x-1 | | -09x+5.52=-0.7x+8.12 | | k/4=-5 | | 5m+2(2m-7)= | | 19-7x=11+5x | | 3(4x+4)=-48 | | 3-x=-24 | | -9x-6x=6-9x | | 2x-(12-2x)=4(3x-8)+4 | | x+2*x+4=140 | | 2(x+5)-3=10x-5 | | 0.4x-0.2(4-x)=3.1 | | 13-(4m+6)=4+4m-13 | | 3x-32=-17 | | (x+3)=81 |